Selection for high-level chloroquine resistance results in deamplification of the pfmdr1 gene and increased sensitivity to mefloquine in Plasmodium falciparum. - Barnes, D A (1992)
A chloroquine resistant cloned isolate of Plasmodium falciparum, FAC8, which carries an amplification in the pfmdr1 gene was selected for high-level chloroquine resistance, resulting in a cell line resistant to a 10-fold higher concentration of chloroquine. These cells were found to have lost the amplification in pfmdr1 and to no longer over-produce the protein product termed P-glycoprotein homologue 1 (Pgh1). The pfmdr1 gene from this highly resistant cell line was not found to encode any amino acid changes that would account for increased resistance. Verapamil, which reverses chloroquine resistance in FAC8, also reversed high-level chloroquine resistance. Furthermore, verapamil caused a biphasic reversal of chloroquine resistance as the high-level resistance was very sensitive to low amounts of verapamil. These data suggest that over-expression of the P-glycoprotein homologue is incompatible with high levels of chloroquine resistance. In order to show that these results were applicable to other chloroquine selected lines, two additional mutants were selected for resistance to high levels of chloroquine. In both cases they were found to deamplify pfmdr1. Interestingly, while the level of chloroquine resistance of these mutants increased, they became more sensitive to mefloquine. This suggests a linkage between the copy number of the pfmdr1 gene and the level of chloroquine and mefloquine resistance.